Reporting characteristics of nonsurgical periodontal therapy trials registered in ClinicalTrials.gov: an observational study - Petra Stazic; Diana Juric; Antonela Turic; Antonio Sosic; Ana Marusic; Marija Roguljic (Becaris Publishing Limited, 2023)
Aim: To evaluate the completeness of the description of nonsurgical periodontal therapy interventions in clinical trials registered in ClinicalTrials.gov and correspondence of registered information for trial participants and outcome measures with published articles. Materials & methods: We retrieved data from ClinicalTrials.gov and corresponding publications. The completeness of intervention reporting was assessed using the Template for Intervention Description and Replication (TIDieR) checklist for oral hygiene instructions (OHI), professional mechanical plaque removal (PMPR), and subgingival instrumentation, antiseptics and antibiotics. The completeness of registration of trial protocol information was assessed according to the WHO Trial Registration DataSet for participant information (enrollment, sample size calculation, age, gender, condition) and primary/secondary outcome measures. Results: 79 included trials involved OHI (n = 38 trials, 48.1%), PMPR (n = 19, 24.1%), antiseptics (n = 11, 12.7%), or antibiotics (n = 11, 12.7%). There was a great variety in the terms used to describe these interventions. Most of the analyzed trials (93.7%) were completed and did not provide any data on study phase (74.7%). The description of intervention in the registry in ClinicalTrials.gov was inadequate for all analyzed interventions, with description inconsistencies in matching publications. There were also discrepancies in registered and published outcomes: for 39 trials with published results, 18 had different registered and reported primary outcomes, and 29 different registered and reported secondary outcomes. Conclusion: The completeness of the description of nonsurgical therapy of periodontitis in clinical trials is unsatisfactory, reducing the quality of translation of the new evidence and procedures into clinical practice. Significant discrepancy in registered and reported trial outcomes calls into question the validity of reported results and relevance for practice.